Data breach on the critical information infrastructures: lessons from the Wikileaks - Abdul Ghani Azmi, Ida Madieha; Zulhuda, Sonny; Jarot, Sigit Puspito Wigati (IEEE, 2012)
The recent massive critical data leaks by Wikileaks suggest how fragile national security is from the perspective of information system and network sustainability. This incident raises some causes of concern. Firstly, critical infrastructure such as military and diplomatic systems is not spared from security breach. Secondly, such leak causes far-reaching damage to public interests, national security and economic sustainability. And thirdly, both technology and law seem incapable of dealing with such situation. Malaysia is not spared from the risk of information security attacks. Its ten critical sectors as identified in its National Cyber Security Policy (NCSP) –national defence and security; banking and finance; information and communications; energy, transport and water; government, emergency and medical services; as well as food and agriculture– can at any time fall victim to security breaches and data leaks if efforts to protect their system are flawed.